Laparoscopic Pectopexy - Palmas, Artur (2017)
Different operative approaches for the repair of a genital prolapse have been reported. However, for the reconstitution of a physiological axis of the vagina, a sacropexy seems to be the most adequate approach. We describe a method of laparoscopic apical prolapse surgery, where the lateral parts of the iliopectineal ligament are used for a bilateral mesh fixation of the descended structures. The iliopectineal ligament is a stable structure for the fixation of meshes and sutures, statistically significant stronger than the sacrospinous ligament and arcus tendinous of pelvic fascia. The incidence of defecation disorders, are reduced by a more physiological lateral fixation, which does not reduce the pelvic space. We used a single-port transumbilical device, with an additional 5 mm port, where at the end of the procedure, the drain is placed. This technique, a virtually scarless surgery, represents also, an option for women, who have an esthetic concern about scars.